2021
DOI: 10.1371/journal.ppat.1009869
|View full text |Cite
|
Sign up to set email alerts
|

BB0562 is a nutritional virulence determinant with lipase activity important for Borrelia burgdorferi infection and survival in fatty acid deficient environments

Abstract: The Lyme disease spirochete Borrelia burgdorferi relies on uptake of essential nutrients from its host environments for survival and infection. Therefore, nutrient acquisition mechanisms constitute key virulence properties of the pathogen, yet these mechanisms remain largely unknown. In vivo expression technology applied to B. burgdorferi (BbIVET) during mammalian infection identified gene bb0562, which encodes a hypothetical protein comprised of a conserved domain of unknown function, DUF3996. DUF3996 is also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Fractionation of B. burgdorferi lysate into soluble and membrane fractions was performed as previously described (Kuhn et al, 2021). Briefly, wild‐type B. burgdorferi was grown to a density of ~1 × 10 8 cells/ml in BSK‐II medium.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fractionation of B. burgdorferi lysate into soluble and membrane fractions was performed as previously described (Kuhn et al, 2021). Briefly, wild‐type B. burgdorferi was grown to a density of ~1 × 10 8 cells/ml in BSK‐II medium.…”
Section: Methodsmentioning
confidence: 99%
“…The fusion construct was verified by restriction digest and Sanger sequencing. The pET43.1b‐ glpD opt plasmid was moved to NiCo21 (DE3) E. coli (New England Biolabs) for protein induction and purification, as previously described (Kuhn et al, 2021) (Figure S2). The glycerol 3‐phosphate dehydrogenase activity of recombinant Nus‐GlpD and Nus alone in the presence and absence of 10 μM FAD was determined using the G3PDH colorimetric assay kit (Abcam).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the study compared PC uptake in different bacteria and revealed that such uptake was specific to Borrelia and likely acquired by random diffusion. Borrelia lipase (bb0562) contributes to fatty acid scavenging and Borrelia survival under conditions in which free fatty acids are limited (12), but a comprehensive understanding of uptake will require further work. Gwynne and co-authors also demonstrated that the ratio of environmental lipids found in the growth media directly correlated with the proportion of lipids found in the Borrelia membrane (4).…”
Section: Dependence Of Borrelia On Host Lipidsmentioning
confidence: 99%